1992
DOI: 10.1063/1.107196
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from electron-hole plasmas confined in Si/Si1−xGex/Si quantum wells

Abstract: We report the first observation of photoluminescence from electron-hole plasmas in Si/S&,sGe&Si quantum wells. While at liquid helium temperature, luminescence due to shallow bound excitons is observed. At 77 K electron-hole plasma (EHP) luminescence dominates the spectra over a wide range of pump powers. Convolution of the occupied electron and hole densities of states gives an excellent fit to the photoluminescence line shape. A bandgap reduction of up to 15 meV at high carrier densities is observed for wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The spectral shape of radiative recombination of electrons and holes in their degenerate systems is given by convolution of the occupied electron and hole densities of state: 11,12,15 I͑h…”
Section: Electron-hole Condensation In Simentioning
confidence: 99%
“…The spectral shape of radiative recombination of electrons and holes in their degenerate systems is given by convolution of the occupied electron and hole densities of state: 11,12,15 I͑h…”
Section: Electron-hole Condensation In Simentioning
confidence: 99%
“…One can use the model presented in [14] for description of the recombination processes in the semiconductor. The model is based on the calculation of the occupation of the states available in the conduction and the valence bands at certain concentration of minority carriers and certain electric field in the semiconductor.…”
Section: Figurementioning
confidence: 99%
“…That field confines the carriers and keeps them close to the recombination active centres. The authors showed that the emission line shape of the MISLED can be fitted by the electron-hole-plasma recombination model [14]. Additionally, there has been indication of radiative recombination between the electrons and holes via the interface states.…”
Section: Introductionmentioning
confidence: 97%
“…To extract The details of this model is given in Ref. 8. The fitted spectra are shown in Fig.5(b) as well as the contribution from the NP line only.…”
Section: Photoluminescencementioning
confidence: 99%